2021
DOI: 10.1111/jocn.15915
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic control mediates the relationships of employment status and self‐stigma with self‐care behaviours in young adults with type 2 diabetes

Abstract: Aims and objectives:To investigate the relationships of sociodemographic factors, self-stigma, glycaemic control (measured by glycated haemoglobin (A1C)) and selfcare behaviours in young adults with type 2 diabetes.Background: Young adults aged 25-44 years are in their most productive period.Once diagnosed with diabetes, this population tends to experience poor glycaemic control and perform poorly in self-care activities. Such patterns may raise perceptions of self-stigma and further decrease motivations to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…This report is attached to the patient's medical records and contains all of the findings and conclusions from the first evaluation, as well as directions for nurses and caregivers written in clear language and providing suitable monitoring schedules (dates for future consultations and tests). Strict record-keeping with the addition of any new information that is relevant, particularly any changes in treatment and test results, will serve to flag any unusual occurrences and provide an easily accessible resource for everyone involved in the patient's care, particularly those who are not familiar with the patient 61,6 . This is especially important for those who are not familiar with the patient.…”
Section: Feet and Peripheral Neuropathymentioning
confidence: 99%
“…This report is attached to the patient's medical records and contains all of the findings and conclusions from the first evaluation, as well as directions for nurses and caregivers written in clear language and providing suitable monitoring schedules (dates for future consultations and tests). Strict record-keeping with the addition of any new information that is relevant, particularly any changes in treatment and test results, will serve to flag any unusual occurrences and provide an easily accessible resource for everyone involved in the patient's care, particularly those who are not familiar with the patient 61,6 . This is especially important for those who are not familiar with the patient.…”
Section: Feet and Peripheral Neuropathymentioning
confidence: 99%
“…This result supported the results of similar studies in the literature. 5,[11][12][13][14]22,28,29 Kato et al 13 reported a strong negative predictive effect of self-stigma on the self-care behaviors of people with T2DM. Brazeau et al 11 stated that in diabetic young people, stigmatization was associated with lower self-efficacy levels, higher A1c levels, severe hypoglycemia, and reduced feelings of wellbeing.…”
Section: (mentioning
confidence: 99%
“…In addition, studies have shown that stigma perceived by people with diabetes affects their DM management negatively. 5,[11][12][13][14] Kato et al 5 reported that internalized stigma had a negative effect on the self-management of people with T2DM. In another study by Kato et al 13 a negative relationship was found between the self-stigma levels and self-care behaviors of people with T2DM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Psychologically, stigma lowers self-efficacy and self-esteem, and increases stress in diabetics , [10] which leads to engagement in less healthy behaviors, and as a result glycosylated hemoglobin, is found to be adversely affected by diabetes-related stigma. [7][8][9] There is urgent need for research in the area of stigma [19] that includes documenting the magnitude and nature of diabetesrelated stigma, comparing stigma in different settings, and identifying its determinants. [11] Moreover, according to our knowledge, studies investigating diabetes-related social stigma (DRSS) is explored less than the other types.…”
Section: Introductionmentioning
confidence: 99%